Wound healing effect of acanthaster planci sulfated glycosaminoglycans extracted from diabetic induced rats - Zainudin, Nur Hanim (2018)
The Crown-of-Thorns starfish is an echidonermata that inhabits tropical and subtropical marine ecosystem within the Indo-Pacific. The starfish: A. Planci causes endemic devegetation of coral reef ecosystem. This study extrapolate a industrial able effort to exploite the starfish biomass as strategy management. In this millinea, the strategic management of the starfish: A. Planci is a dilemma. High content of GAGs can be extracted from COT’s starfish: A. Planci biomass. The main aim of this study was to harness the prowess of wound healing capabilities of COT’s starfish: A. Planci sulfated GAGs extracted from its body’s coelomic fluid and body’s integument wall in management of chronic (diabetic) wound. Macroscopic observation (wound contraction and inflammatory response) and microscopic assessment (LM and FEGSEM) was adapted to discuss the important features and histological analysis findings related to epithelial cell migration, collagen fibers reorganization, PMNL and fibroblasts cell proliferation and the formation of new blood vessels (angiogenesis). Three concentrations dose of 1 μg/ml, 3 μg/ml and 5 μg/ml were topically applied on the full thickness excision wound at the streptozotocin (STZ) induced diabetic Sprague Dawley male rats. Applications of 10 mg from 1 μg/ml, 3 μg/ml and 5 μg/ml doses of GAGs concentrations applied within a 6mm diameter wound were integrated with carbopolbased transdermal polymer from day 0 to day 12. The wound contraction percentage was significantly (p <0.0167), in sulfated GAGs from COT’s starfish: A. Planci body'scoelomic fluid of 5 μg/ml concentration study as compared to control group. The results revealed that GAGs with 5 μg/ml doses accelerated patho-physiology dynamics of epithelial cell migration far better and significantly (p <0.0167) than as observed in the control group. However there were no recorded differences between the median score for epithelial cell migration from the treatment group when both doses of extracts was analysed. Assessment from the LM and FEGSEM data revealed complete epithelial bridging of the wound area to all treatment groups on day 12. There is a reduction in the presence of macrophage and PMNL cells (polymorphonuclear leukocytes cells) and mast cells in all treatment and control groups. There was no statistical difference on day 12. The increase in fibroblast cell proliferation (p <0.0167) was observed in the treatment group (with coelomic fluid concentration of 5 μg/ml). The formation of new blood vessels was significantly (p <0.05) in the group treated with body’s coelomic fluid. Groups with extracts from coelomic fluid was observed able to stimulate reorganization of collagen fibers, especially on day 12 (p <0.05). This study seems to reveal that GAGs from starfish biomass with different concentration levels manifest different wound healing dynamic features. However, the extracts from coelomic fluid (5 μg/ml concentrations) showed the optimum effect of wound healing, especially in chronic inflammation (on STZ induced diabetic rats models). This discovery gives new hope to the management problem of diabetic wound healing